The Impact of Islamic Banking on the Quality of Banking Services Provided to Customers: A Field Study on Al-Jumhouria Bank - South Tripoli - Mohammed Ali Abdullah (Al-imad Journal of Humanities and Applied Sciences (AJHAS), 2026)
This study aimed to identify the impact of Islamic banking on the quality of banking services provided to customers. The researcher adopted the descriptive–analytical approach, and the study relied on a questionnaire as the main data collection tool. The study sample consisted of customers of the Islamic Bank, South Tripoli branch, where (389) questionnaires were distributed. A total of (383) valid questionnaires were retrieved, representing (98.46%), while approximately (6) questionnaires were lost, representing (1.5%), The study reached several results, the most important of which is the existence of a significant impact of Islamic banking on the quality of banking services provided to customers. This result is supported by the significance level of the F-test, which reached (0.00), being less than the adopted significance level of (0.05). In addition, the value of the coefficient of determination (R²) reached (0.495), indicating that only (49.5%) of the changes in the average responses of the sample regarding the quality of banking services provided to customers are attributed to changes in Islamic banking. Furthermore, the study concluded that there is a need to introduce new methods to gain customer satisfaction. These methods lie in developing and restructuring traditional practices in a way that instills a high level of satisfaction among customers. Banks should also take into consideration that these methods emphasize to customers the avoidance of usury (riba) and interest.